The Influence of Pedagogical Competence, Social Competence, Personal Competence and Professional Competency on Performance Islamic Religious Education Teacher at Muhammadiyah Middle School, Banjar Regency, South Kalimantan Province. (June 2022) - F, F; Kadir, Kadir; A., A.; Abdurrakhman, Abdurrakhman; Z., M.
No abstract available